HYDROGEN ABSORPTION AND STRUCTURE DESTRUCTION OF MACHINERY AND MECHANISM STEEL PARTS IN HYDROGEN-CONTAINING MEDIUM - N. V. Spiridonov (Nauka i Tehnika, 2014)
Hydrogen is one of the most widespread chemical elements in the nature. Molecular hydrogen reacts with a few chemical elements but when hydrogen becomes a radical it interacts with a lot of elements. Metal saturation with hydrogen leads to hydrogen absorption and destruction. The paper presents chronology and essence of processes pertaining to mechanism of hydrogen absorption , hydrogen wear and metal destruction that have been obtained on the basis of the scientific investigation and experimental data analysis.